Review of Economics : Jahrbuch für Wirtschaftswissenschaften (De Gruyter Oldenbourg, 2007)
The Review of Economics (Jahrbuch für Wirtschaftswissenschaften) is a peer-reviewed general interest journal publishing articles from all fields of economics with a strong policy focus. The journal aims to provide a forum for policy contributions and to influence the public debate.